Pengembangan Sumber Daya Manusia dalam dunia Pendidikan - Nur Dzaedzatul H; Sunarto Sunarto (Universitas Palangka Raya, 2025)
This research aims to explore the development of human resources in the field of education. HR development is a series of activities aimed at improving the quality and abilities of employees in the organization. This is not just training, but also includes the process of identifying needs, planning, implementing and evaluating existing development programs. Human resource development is carried out in order to improve a person's quality, which in time will increase productivity. The results of various studies show that the quality of human resources is a determining factor in productivity. In the world of education, human resource development has a very crucial role. The reason is, the quality of education really depends on the quality of the educators. Teachers, lecturers and other educational staff are the spearheads of the learning process. The main aim of human resource development is to improve the quality of learning, so that it has an impact on increasing student achievement and overall school progress. Therefore, investment in developing educational human resources is an investment in the nation's future. By increasing quality educational human resources, educational institutions will become more advanced and developed.